1996
DOI: 10.1021/jp953397f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of the Reaction of F Atoms with CH3Br

Abstract: The reaction of F atoms with CH 3 Br at 296 K was studied using a pulse radiolysis/transient UV absorption spectroscopy absolute technique and a FTIR relative rate technique. The rate constant for this reaction was determined to be (4.46 ( 0.22) × 10 -11 . The reaction proceeds via two channels, 69 ( 5%, via hydrogen abstraction giving CH 2 Br radicals and HF, and 31 ( 5%, to give the adduct CH 3 Br--F. In the FTIR system the observed rate constant was 69 ( 8% of that measured using the pulse radiolysis system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 20 publications
(89 reference statements)
7
28
1
Order By: Relevance
“…The values of k 1 obtained by Masaki et al [15] are independent of total pressure in the pressure range 0.77 -7.7 mbar. This is, however, in line with the results reported by Sehested et al [7] who found that k 1 is independent of total pressure in the pressure range 0.77 -7.7 mbar within 25%. This was explained by the following mechanism for reaction (1):…”
Section: Rate Constants For the Ch 3 Och 2 ϩ O 2 Reactionsupporting
confidence: 93%
See 3 more Smart Citations
“…The values of k 1 obtained by Masaki et al [15] are independent of total pressure in the pressure range 0.77 -7.7 mbar. This is, however, in line with the results reported by Sehested et al [7] who found that k 1 is independent of total pressure in the pressure range 0.77 -7.7 mbar within 25%. This was explained by the following mechanism for reaction (1):…”
Section: Rate Constants For the Ch 3 Och 2 ϩ O 2 Reactionsupporting
confidence: 93%
“…Sehested et al [7] obtained values for k prod,0 , and k RO2,0 , and k RO2,ϱ relative to k CH3OCH2ϩC12 of cm 3 and Sehested et al [7] determined using the absolute rate constants obtained in this work and those obtained by Masaki et al [15]. Hence, only the rate constant ratios k RO2,ϱ /k prod,0 and k RO2,ϱ /k prod,0 obtained in this work and the work of Sehested et al [7] can be compared directly.…”
Section: Rate Constants For the Ch 3 Och 2 ϩ O 2 Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, bromomethylperoxy radical (CH 2 BrOO) can be generated via reaction CH 2 Br + O 2 in the atmosphere (especially in the marine boundary layer), while the CH 2 Br radicals are formed via abstraction of a hydrogen atom from CH 3 Br by OH or Cl [6,7]. The UV absorption spectrum of gaseous CH 2 BrOO has been studied, revealing a broad and structureless feature at 240 nm [2,4,8]. The rate coefficient [4] of its self-reaction has been determined to be (1.1 ± 0.4) Â 10 À12 cm 3 molecule À1 s À1 at 298 K. Recently, the IR spectrum of CH 2 BrOO has been studied by Huang and Lee [9].…”
Section: Introductionmentioning
confidence: 99%